RESENHA: MORAES, Antônio Carlos Robert. - Alfredo, Anselmo (Boletim Paulista de Geografia, 2017)
Bases da Formação Territorial do Brasil. Território Colonial Brasileiro no “Longo” Século XVI. São Paulo: Hucitec, 2000. Anselmo Alfredo